2014
DOI: 10.1111/jcmm.12209
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 regulates vimentin expression via miR‐30a during epithelial–mesenchymal transition in gastric cancer cells

Abstract: Runt-related transcription factor 3 (RUNX3) is a putative tumour suppressor via regulating the expression of a series of target genes. Clinical studies demonstrated that loss of RUNX3 expression is associated with gastric cancer progression and poor prognosis, but the underlying mechanism is not entirely clear. Accumulating evidence shows that the epithelial–mesenchymal transition (EMT) plays an important role in cancer relapse and metastasis. Therefore, we addressed whether RUNX3 has a role in the EMT in gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…Previous studies demonstrated that miR-30 can promote autophagy by beclin 1, 17,18 suppress growth and metastasis by targeting metadherin or denticleless protein homolog (DTL), [19][20][21] inhibit epithelial-to-mesenchymal transition by targeting Snai1, 22 and inhibit migration and invasion by downregulating vimentin expression. 23,24 Only a few studies reported that miR-30a existed in exosomes, and the levels of miR-30a derived from exosomes in urine, serum or plasma, and saliva could be used as non-invasive biomarkers for screening and diagnosing a certain type of cancer. [25][26][27] Our results indicate that hundreds of particular miRNAs were upregulated in exosomes from cancer cells compared with that from normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that miR-30 can promote autophagy by beclin 1, 17,18 suppress growth and metastasis by targeting metadherin or denticleless protein homolog (DTL), [19][20][21] inhibit epithelial-to-mesenchymal transition by targeting Snai1, 22 and inhibit migration and invasion by downregulating vimentin expression. 23,24 Only a few studies reported that miR-30a existed in exosomes, and the levels of miR-30a derived from exosomes in urine, serum or plasma, and saliva could be used as non-invasive biomarkers for screening and diagnosing a certain type of cancer. [25][26][27] Our results indicate that hundreds of particular miRNAs were upregulated in exosomes from cancer cells compared with that from normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…These genes include PIK3CD [3], VIM [10], SEPT7 [12], DLL4 [9], CD99 [8], LOX [7], DTL [4], IRS2 [5], FOXL2 [13], etc. In addition, the signaling pathways of miR-30a implicated in the pathogenesis of cancers have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear now that miRNAs perform their biological functions by guiding the RNA-induced silencing complex (RISC) toward 3′ UTR of target mRNAs [2]. miR-30a locates in human chromosome 6q13 and increasing evidence indicates that miR-30a can act as a tumor suppressor to inhibit the growth of various tumors including colorectal carcinoma [3][4][5], breast cancer [6], anaplastic thyroid cancer [7], Ewing's tumor [8], clear cell renal cell carcinoma [9], gastric cancer [10], and nasopharyngeal carcinoma [10,11]. In addition, miR-30a also shows the feature of an oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…To date, >200 miRNAs have been found to be associated with gastric cancer development, progression, and therapeutic response, and numerous studies have indicated that miRNAs may play an important role in the MDR of various types of cancer, including gastric cancer (9)(10)(11). It has previously been reported that miR-30a is significantly downregulated in gastric cancer cells (12,13). However, there is a lack of research on whether miR-30a regulation can affect the chemosensitivity of resistant gastric cancer cells, and the underlying mechanisms regarding the potential effects of miR-30a on drug resistance and cell autophagy require further investigation.…”
Section: Introductionmentioning
confidence: 99%